Factors that influence the prescription of physical activity: a cross sectional survey - Roxana Diana Argeșanu; Cosmina Iustina Mogoș; Maria Alexandra Cucu; Petru Armean; Eugenia Claudia Bratu; Lăcrămioara Aurelia Brîndușe (Balneo and PRM Research Journal, 2023)
The study aims to assess the health professionals' knowledge, attitudes, and practices toward the evaluation and prescription of PA (physical activity) to develop public health measures to improve PA preventive interventions.; Methods: A cross‐sectional study, using a confidential self‐administered questionnaire applied to health practitioners involved in individual preventive services related to PA in Romania, was conducted. The internal consistency of the questionnaire was explored, and the data were analyzed with descriptive and inferential statistics; Results: A total number of 464 health professionals (community nurses, family doctors, and other professional categories) completed all questionnaire. We found differences in knowledge distribution, with the lowest level for nurses (p<0.001). Women have a positive attitude toward PA counselling compared to men (p=0.037).The patient’s nutritional status (89.2%) and positive attitudes towards PA (42.0%) are the most mentioned factors that positively influence the PA prescription. Among barriers to prescribe PA, the most health professionals list: patient low compliance (65.3%) and lack of systematic training (63.8%); Conclusions: The participants have relatively good knowledge and positive attitudes toward the importance of PA. They feel self-confident and need public health support for systematic training, health-promoting resources, and national guidelines.